Assessment of treatment and monitoring patterns and subsequent outcomes among patients with chronic myeloid leukemia treated with imatinib in a community setting. (April 2014) - Saleh, Mansoor N.; Haislip, Sally; Sharpe, Joyce; Hess, Tamara; Gilmore, James; Jackson, James; Sail, Kavita R.; Ericson, Solveig G.; Chen, Lei
Abstract Introduction: Real-world treatment and monitoring patterns have not been well documented among imatinib-treated chronic phase chronic myeloid leukemia (CP-CML) patients. Thus, we evaluated these patterns and responses to imatinib in CP-CML patients. Methods: This retrospective study, based on the Georgia Cancer Specialists' electronic medical record (EMR) system, identified CP-CML patients initiating treatment with imatinib from 01/01/2002 to 11/01/2011 who were subsequently followed for ≥6 months. Results: A total of 177 patients met the study criteria. Imatinib dose modification occurred in 59 patients (33%). Rates of treatment interruption, discontinuation, and switching to another therapy were 16%, 24%, and 23%, respectively. Of 27 patients discontinuing imatinib for lack of efficacy, 9 (33%) had initial dose escalation; 26 patients (96%) eventually switched to a second-generation tyrosine kinase inhibitor. By 3 months, 168 patients remained on imatinib, of whom 96 (57%) had undergone cytogenetic and/or molecular testing. The frequency of response monitoring fluctuated over time, with rates as high as 28% for cytogenetic and 69% for molecular testing. Cumulative response rates steadily increased; 18 month rates were 47% for complete cytogenetic response and 26% for major or complete molecular response. There were no cases of progression and/or death among 38 patients who were regularly monitored for molecular response within the first 12 months of imatinib. Ten of 98 patients (10%) not regularly monitored had progressed or died. Conclusions: Almost one-third of patients initiating imatinib for CP-CML required dose modification, treatment interruption, or discontinuation. Opportunities for improved monitoring in this setting were identified. Limitations include those inherent to retrospective analyses based on EMR and the uncertain extrapolability of the results.